Fabrication and electrical characterization of transparent NiO/ZnO p-n junction by the sol-gel spin coating method - Cavas, M.; Gupta, R. K.; Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2012)
Sol-gel spin technique was used to fabricate transparent p-n junction between NiO and ZnO semiconductors. Atomic force microscopy studies indicated that ZnO film had a fibrous structure, while NiO film showed very smooth surface morphology. The optical transmittance of these films was about 75 %. The optical band gaps of ZnO and NiO films were obtained to be 3.25 and 3.89 eV, respectively. The current-voltage characteristics of NiO/ZnO junction showed a good rectifying behavior. The junction parameters such as ideality factor and barrier height were calculated using thermionic emission model. The barrier height and ideality factor values of the diode were obtained to be 0.48 and 2.91 eV, respectively. The variation of photocurrent with wavelength indicates that this device had high efficiency in wavelength range of 450-475 nm.
Keywords: p-n junction; ZnO; NiO; Sol-gel Thin films; Semiconductor